2015
DOI: 10.1111/pai.12452
|View full text |Cite
|
Sign up to set email alerts
|

Dust mite avoidance for the primary prevention of atopic dermatitis: A systematic review and meta‐analysis

Abstract: Dust mite avoidance strategies alone or in combination with additional allergen avoidance modalities do not decrease the risk of developing atopic dermatitis and, given the current state of the evidence, should not be recommended for this purpose. The utility of dust mite avoidance for the treatment of atopic dermatitis or for the prevention and treatment of asthma or seasonal rhinoconjunctivitis are outside the scope of this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 57 publications
0
10
0
1
Order By: Relevance
“…Strategies to prevent AD and FA have focused on limiting exposure to potential allergens, early introduction of complementary foods, supplementing diet with probiotics, and unsaturated fatty acids . As dust mites may play a role in the pathophysiology of AD, avoidance strategies have been evaluated to reduce the risk of developing AD in high‐risk infants compared to randomized controls . However, at the moment, it is not possible to determine clear implications from the very low‐quality evidence currently available and dust mite avoidance should not be recommended for this purpose .…”
Section: Prevention Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategies to prevent AD and FA have focused on limiting exposure to potential allergens, early introduction of complementary foods, supplementing diet with probiotics, and unsaturated fatty acids . As dust mites may play a role in the pathophysiology of AD, avoidance strategies have been evaluated to reduce the risk of developing AD in high‐risk infants compared to randomized controls . However, at the moment, it is not possible to determine clear implications from the very low‐quality evidence currently available and dust mite avoidance should not be recommended for this purpose .…”
Section: Prevention Strategiesmentioning
confidence: 99%
“…78 As dust mites may play a role in the pathophysiology of AD, avoidance strategies have been evaluated to reduce the risk of developing AD in high-risk infants compared to randomized controls. 79 However, at the moment, it is not possible to determine clear implications from the very low-quality evidence currently available and dust mite avoidance should not be recommended for this purpose. 80 There has been a long-standing debate on allergy prevention by reducing or increasing exposure to food allergens, delaying or advancing weaning.…”
Section: Prevention Strategiesmentioning
confidence: 99%
“…The causal role of allergen as the driver of AD has been debated for over a decade [13]; prevailing theories consider both skin barrier defects and cellular immune deviations as contributors to increased sensitization to environmental allergens in AD [14]. More simply said, allergen exposure without both barrier disruption and involvement of adaptive immune recognition is not sufficient to elicit an allergic response [15], and allergen avoidance in the absence of preventing skin barrier disruption is unlikely to protect against allergy [16]. The public health importance of pinpointing the causal factors in AD is further demonstrated by the strong association between onset of AD in infancy and future development of food allergy [17] and asthma [18, 19].…”
Section: The Role Of Skin In Allergymentioning
confidence: 99%
“…Morgan et al found that 1 year after invention, asthma‐associated morbidity decreased in asthmatic children belonging to the intervention group with reduced allergen concentrations in beds and on the bedroom floor. Recent analyses of birth cohorts and intervention studies, however, challenge the longtime benefit of allergen avoidance, as no association between early allergen exposure and risk of sensitization or allergic symptoms could be found . However, allergen exposure was not always proven by measurements in these studies, and even if allergens were quantified, reservoir dust from beds or floors in homes was used.…”
Section: Introductionmentioning
confidence: 99%